The Bible and counselling - Hurding, Roger (London, Hodder & Stoughton, 1992)
Roger Hurding's The Bible and Counselling is the definitive guide to the relationship between Christian caring and counselling, by one of Britain's foremost Christian counsellors and psychotherapists
Keywords: Counseling.-- Religious aspects.-- Christianity; Pastoral Counseling